Community awareness about tangible and intangible benefits of Sibuti Mangrove Forest, Sarawak, Malaysia - Shah, Kaleem; Mustafa Kamal, Abu Hena; Adrain, Daud; Rosli, Zamri; Hakeem, Khalid Rehman; Hoque, Mohd Nesarul (Forest Research Institute Malaysia, 2016)
Mangrove forest is highly productive and provides enormous tangible and intangible benefits to the local communities. Millions of people are dependent on mangrove for their livelihoods around the world including Malaysia. Many researchers in Malaysia have focused on ecological and environmental aspects of mangroves; however very few research works are documented on social linkage aspect to this unique characteristic of forest particularly in Sarawak. Hence, this study focuses on community awareness about the benefits of Sibuti mangrove forest to the local community in Sarawak. Data was recorded from 60 respondents using simple random sampling techniques in three villages surrounding Sibuti mangrove forest through structured and semi-structured interview schedule. The coastal community was not depending on Sibuti mangroves forest in terms of direct benefits, however, low dependency was recorded on mangrove forest in term of crab and mollusk collection (55%), Nypa fruits collection (35%) and Nypa leaves collection (32%). Fishing was the only direct benefit, which was getting by the community (48%) from Sibuti mangrove forest and adjacent areas. The community believed that mangrove forest provide them indirect benefits such as breeding ground of fish, protecting their land from soil erosion, contributing towards land formation, filtering the water resource, increasing scenic view, providing food to the fish, working as nutrients hub for fishes, wildlife habitat, protection from floods, protection from cyclones/storms/tornados and protecting them from Tsunami. Most of the respondents were always willing to play role in the development of Sibuti mangroves, interested in learning about conservation and protection practices, while some (62%) were ready for volunteer role in conservation and protection if assign to them. Most of them i.e., 60% were ready to play role as volunteer and 77% was ready to work as facilitator. Majority (53%) was willing to pay donations. The educational, research and training program were welcomed by 98% of the respondents. The findings of the study suggest that forestry resource could be managed through community involvement for the well being of fishery resources, community livelihoods, wildlife and eco-tourism development.